Cholesterol‐imprinted macroporous monoliths: Preparation and characterization. Issue 22 (26th September 2017) - Stepanova, Mariia А.; Kinziabulatova, Lilia R.; Nikitina, Anna A.; Korzhikova‐Vlakh, Evgenia G.; Tennikova, Tatiana B.
Abstract: The development of sorbents for selective binding of cholesterol, which is a risk factor for cardiovascular disease, has a great importance for analytical science and medicine. In this work, two series of macroporous cholesterol‐imprinted monolithic sorbents differing in the composition of functional monomers (methacrylic acid, butyl methacrylate, 2‐hydroxyethyl methacrylate and ethylene dimethacrylate), amount of a template (4, 6 and 8 mol%) used for molecular imprinting, as well as mean pore size were synthesized by in situ free‐radical process in stainless steel housing of 50 mm × 4.6 mm i.d. All prepared materials were characterized regarding to their hydrodynamic permeability and porous properties, as well as examined by BET and SEM methods. Imprinting factors, apparent dynamic dissociation constants, the maximum binding capacity, the number of theoretical plates and the height equivalent to a theoretical palate of MIP monoliths at different mobile phase flow rates were determined. The separation of a mixture of structural analogues, namely, cholesterol and prednisolone, was demonstrated. Additionally, the possibility of using the developed monoliths for cholesterol solid‐phase extraction from simulated biological solution was shown.